Exploring the Functional Properties of Leaves of Moringa oleifera Lam. Cultivated in Sicily Using Precision Agriculture Technologies for Potential Use as a Food Ingredient - Carlo Greco; Graziella Serio; Enrico Viola; Marcella Barbera; Michele Massimo Mammano; Santo Orlando; Elena Franciosi; Salvatore Ciulla; Antonio Alfonzo; Rosario Schicchi; Daniela Piazzese; Carla Gentile; et al. (Antioxidants)
This study aimed to evaluate the microbiological quality and functional properties of Moringa oleifera Lam. leaves from plants cultivated in Sicily, with the objective of exploring their potential use in functional food production. Precision agriculture techniques, including unmanned aerial vehicle-based multispectral remote sensing, were used to determine the optimal harvesting time for M. oleifera. After harvesting, leaves were dried using a smart solar dryer system based on a wireless sensor network and milled with a laboratory centrifugal mill to produce powdered M. oleifera leaves (PMOLs). Plate counts showed no colonies of undesired microorganisms in PMOLs. The MiSeq Illumina analysis revealed that the class Alphaproteobacteria was dominant (83.20% of Relative Abundance) among bacterial groups found in PMOLs. The hydroalcoholic extract from PMOLs exhibited strong redox-active properties in solution assays and provided antioxidant protection in a cell-based lipid peroxidation model (CAA50: 5.42 μg/mL). Additionally, it showed antiproliferative activity against three human tumour epithelial cell lines (HepG2, Caco-2, and MCF-7), with GI50 values ranging from 121.03 to 237.75 μg/mL. The aromatic profile of PMOLs includes seven phytochemical groups: alcohols, aldehydes, ketones, esters, acids, terpenes, and hydrocarbons. The most representative compounds were terpenes (27.5%), ketones (25.3%), and alcohols (14.5%). Results suggest that PMOLs can serve as a natural additive for functional foods.